Unbundling the effect of prior invention experience from firm size on future exploratory and exploitative search. Issue 2 (3rd April 2017) - Shao, Feibo; Hart, Timothy A.
Abstract: This paper examines the role of prior invention experience on future search activities within the pharmaceutical industry. Specifically, we examine to what extent prior invention experience influences future exploratory and exploitative search behavior by firms. The results indicate there is a negative relationship between prior experience and future exploratory search, but a positive effect of prior experience on future exploitative search. Additionally, we find that these effects are moderated by firm size. Specifically, firm size mitigates the negative relationship between prior experience and future exploratory search, and also weakens the positive relationship between prior experience and future exploitative search.